Variation of voltage supply on energy consumption / Abd Manan Abd Rahman - Abd Rahman, Abd Manan (2003)
In engineering terms, power is the rate of delivering energy and is proportional to the product of the voltage and current. The power supply system can only control voltage supply, it has no control over the currents that that particular loads might drawn. So changes in voltage supply will affect power drawn by the system. This project is aimed to investigate the possibility of saving energy thought reduction of voltage within the allowable voltage limits of supply system.